Development of laser communication system in space-ground integrated information network - Jianfeng SUN (Dianxin kexue)
The space laser communication technology has the advantages of high communication speed,good confidentiality and strong anti-interference ability,and has become a research hot spot in recent years and has been widely used in the space-based information network one after another.First of all,the development trend of international laser communication technology was analyzed.Then based on the demand of our country’s space-ground integrated information network,the laser communication system on different application scenarios was analyzed,and the suggestion of the development of laser communication system in space-ground integrated information network was put forward.